All for students: interviews & speeches - Chang, Vincent (Brac University, 2022)
This book is a collection of selected interviews and speeches I have given since my arrival in Dhaka three years ago. These thought pieces are about students and the transformational experience that a university ought to provide to every single unique one of them. Since then, I have received correspondence and feedback from students of BRAC University and other universities, BRAC University’s alumni and faculty, as well as Bangladeshi diaspora from as far as Argentina, Tanzania, New Zealand, North America and Europe. Some wished to see in a book the thoughts behind these interviews and speeches. This book is perhaps the first step towards that.